VIVALDI ANTIPODAL ANTENNA WITH HIGH GAIN AND REDUCED SIDE LOBE LEVEL USING SLOT EDGE WITH NEW NEOGOTHIC FRACTAL BY CANTOR WITH APPLICATION IN MEDICAL IMAGES FOR TUMOR DETECTION - Figueredo Sobrinho, Raimundo Eider; De Oliveira, Alexandre ManiÃ§oba; De oliveira Neto, Antonio Mendes; Serres, Alexandre Jean Rene; De Alexandria, Auzuir R.; Justo Filho, JoÃ£o Francisco; Perotoni, Marcelo B.; Nurhayati, Nurhayati; Nogueira, Ingrid C. (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2020)
This article addresses the study of the Vivaldi Antipodal Antenna (AVA) seeking to improve the gain, decrease the Side Lobe Level (SLL) and the squint, to make the antenna more directive and obtain a more stable radiation pattern. Its intended application lies in the generation of biological microwave imaging to detect brain tumors. With this objective, the Fractal Slot Edge (FSE) technique was applied with a new fractal developed and based on the Cantor set. The application of this fractal, called Cantor Neogothic Fractal (CNG), formed different-sized cavities resulting, in this work, in three antennas that were analyzed through numerical computational simulation together with AVA. The antennas, called CNG9-FSE-AVA, CNG18-FSE-AVA, and CNG27-FSE-AVA, in which 9, 18, and 27 define the maximum height that the fractal reached in each antenna, have areas equal to 354.66 mm2 , 709.33 mm2 and 1064 mm2 , respectively. All antennas achieved the goal, however, CNG27-FSE-AVA presented the best results at 2 GHz, with a gain of 7.84 dBi, SLL -19.80 dB, and squint of -0.10 degree. Additionally, it was proved that the antenna is suitable to generate a near field microwave imaging of tumors in a brain model.